2015
DOI: 10.1177/1350650115580186
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for the optimization of the thermo-mechanical behaviour of dry-running clutches using fibre-optic sensing technology with high spatial measurement density

Abstract: Measuring temperature in tribological contacts remains being a huge challenge. The present paper proposes a new approach to analyze and optimize the thermo-mechanical behaviour of a dry-running clutch without affecting the real interacting surfaces. Using fibre-optic sensing technology makes it possible to gain a very detailed view of temperature distribution in the system. The interpretation of the measurements for different load situations has shown that the behaviour in the first 0.8 s is very similar. But … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A variety of engineering techniques, such as optical fiber sensors, were used to study the temperature distribution during sliding by Jonas, 29 Jen, 25 Ingram, 30 or by Zhao 31 to examine thermal elastic stability. From a study of deformation and instability, Zagrodzki 32 identified that the middle section of the radius is the first to reach the yield limit.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of engineering techniques, such as optical fiber sensors, were used to study the temperature distribution during sliding by Jonas, 29 Jen, 25 Ingram, 30 or by Zhao 31 to examine thermal elastic stability. From a study of deformation and instability, Zagrodzki 32 identified that the middle section of the radius is the first to reach the yield limit.…”
Section: Introductionmentioning
confidence: 99%